Aspergillus and Penicillium species: potential agents for. biocontrol of M acrophomina phaseolina - and C. SEN, B. MUKHERJEE (Indian Phytopathology, 2002)
Four potential fungal antagonists of Macrophomina phaseolina were isolated from soils by general screening and dual cultures, and were identified as Aspergillus fumigatus, A. terreus, Penicillium citrinum and P. simplicissimum. Of these. only A. [umigatus produced sufficient antibiotic principle in cultural filtrate that caused significant inhibition of fungal growth and germination of sclerotia. The priniciple was thermolabile. Mixed culture inoculation after different periods of incubation showed that competitive pre-ernption at food base was the primary mode of action where antibiosis played a secondary role. When applied to soil on a food base. all test antagonists reduced intensity of seedling blight of jute significantly and the effect was dose proportional for the Penicillium spp. The antagonists remained effective for a short duration.